Identification of an alternative nitrogenase system in Rhodospirillum rubrum. - Lehman, L J (1991)
A second nitrogenase activity has been demonstrated in Rhodospirillum rubrum. This nitrogenase is expressed whenever a strain lacks an active Mo nitrogenase because of physiological or genetic inactivation. The alternative nitrogenase is able to support growth on N2 in the absence of fixed N. V does not stimulate, nor does Mo or W inhibit, growth or activity under the conditions tested. The proteins responsible for this activity were identified by electrophoretic and immunological properties. The synthesis of these proteins was repressed by NH4+. The alternative nitrogenase reductase is ADP ribosylated in response to darkness by the system that regulates the activity of the Mo nitrogenase. The genes for the alternative nitrogenase have been cloned, and the alternative nitrogenase reductase has been expressed in an in vitro transcription-translation system.